Lead‐related infective endocarditis with vegetations: Prevalence and impact of pulmonary embolism in patients undergoing transvenous lead extraction. (8th August 2022) - Bontempi, Luca; Arabia, Gianmarco; Salghetti, Francesca; Cerini, Manuel; Dell'Aquila, Andrea; Milidoni, Antonino; Ahmed, Ashraf; Cersosimo, Angelica; Giacopelli, Daniele; Mitacchione, Gianfranco; Raweh, Abdallah; Muneretto, Claudio; et al.
Abstract: Introduction: The prevalence and impact of pulmonary embolism (PE) in patients with lead‐related infective endocarditis undergoing transvenous lead extraction (TLE) are unknown. Methods: Twenty‐five consecutive patients with vegetations ≥10 mm at transoesophageal echocardiography were prospectively studied. Contrast‐enhanced chest computed tomography (CT) was performed before (pre‐TLE) and after (post‐TLE) the lead extraction procedure. Results: Pre‐TLE CT identified 18 patients (72%) with subclinical PE. The size of vegetations in patients with PE did not differ significantly from those without (median 20.0 mm [interquartile range: 13.0–30.0] vs. 14.0 mm [6.0–18.0], p  = 0.116). Complete TLE success was achieved in all patients with 3 (2–3) leads extracted per procedure. There were no postprocedure complications related to the presence of PE and no differences in terms of fluoroscopy time and need for advanced tools. In the group of positive pre‐TLE CT, post‐TLE scan confirmed the presence of silent PE in 14 patients (78%). There were no patients with new PE formation. Large vegetations (≥20 mm) tended to increase the risk of post‐TLE subclinical PE (odds ratio 5.99 [95% confidence interval (CI): 0.93–38.6], p  = 0.059). During a median 19.4 months follow‐up, no re‐infection of the implanted system was reported. Survival rates in patients with and without post‐TLE PE were similar (hazard ratio: 1.11 [95% CI: 0.18–6.67], p  = 0.909). Conclusion: Subclinical PE detected by CT was common in patients undergoing TLE with lead‐related infective endocarditis and vegetations but was not associated with the complexity of the procedure or adverse outcomes. TLE procedure seems safe and feasible even in patients with large vegetations.